(untitled) (Colloquia Comparativa Litterarum, 2025)
The Home of Literature is a metaphor of the literature and literary community. However, this metaphor is connected with the home obsession in contemporary post-Yugoslavian literatures. After the collapse of the Former Yugoslavia and Bosnian war, the home is one of the constant themes in contemporary literature in all area. We can see that in the poetry of the Bosnian-Slovenian poet Josip Osti, but also in the novels and essays of the famous emigrant writer Dubravka Ugrešić, as well as in the works of Peter Semolič, Miljenko Jergović, Vida Ognjenović, Jasna Koteska etc. The home is often present even in the titles of their works (House of Language by Osti, House of Words by Semolič, The House of Dead Scents by Ognjenović), and what is more important – the home is a counterpart of the literature as a place of the sense in the world that every day loses a part of its sense and good taste. The literary home is not a utopian place, because it is a collective image and it could be the dystopian place as well. We mark that through the works about the prison and concentration camps – The Damned Yard by Ivo Andrić, the novels and stories by Danilo Kiš, Dragoslav Mihailović, Branko Hofman, Miroslav Popović etc. At all events, the literary home is always a place of the reinventing of the sense.